ZHX2 in health and disease - Li, Na; Wu, Zhuanchang; Ma, Chunhong (Frontiers in Oncology, 2022)
As a transcriptional factor and the negative regulator of alpha fetal protein (AFP), Zinc fingers and homeoboxes 2 (ZHX2) has a well-established role in protection against hepatocellular carcinoma (HCC). However, recent studies have suggested ZHX2 as an oncogene in clear cell renal cell carcinoma (ccRCC) and triple-negative breast cancer (TNBC). Moreover, mounting evidence has illustrated a much broader role of ZHX2 in multiple cellular processes, including cell proliferation, cell differentiation, lipid metabolism, and immunoregulation. This comprehensive review emphasizes the role of ZHX2 in health and diseases which have been more recently uncovered.